1974
DOI: 10.1159/000152696
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Cystinuria among Jews of Libyan Origin

Abstract: Seven of 24 unrelated Israeli Jewish families affected with cystinuria were of Libyan origin. Five of these seven families were intensively investigated and heterozygotes were identified in four of them. This indicates that, contrary to other populations, in this community cystinuria is mainly of type II or III. Among randomly screened healthy school children of Libyan origin 3–4% were found to be heterozygotes for cystinuria. It is estimated that in this community the frequency of genetically determined cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It has been reported that Libyan Jewish have the highest rate of cystinuria and they mostly suffer non-type I disease. 8,9 This may be the combined result of genetic defects, which are transferred through generations and environmental, dietary, and socioeconomic factors. In our cohort, Jewish origin was not involved in the cystinuria defect and cystine stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Libyan Jewish have the highest rate of cystinuria and they mostly suffer non-type I disease. 8,9 This may be the combined result of genetic defects, which are transferred through generations and environmental, dietary, and socioeconomic factors. In our cohort, Jewish origin was not involved in the cystinuria defect and cystine stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of cystine stones often occurs in the second or third decade in cystinurics but may begin at an earlier age in certain individuals. The incidence of cystinuria varies worldwide from 1/2,500 among Israeli Jews of Libyan origin [Weinberger et al, 1974] 600918) are inherited in an incomplete recessive manner. Patients with homozygous cystinuria have elevated urinary excretion of cystine and dibasic amino acids and in contrast to type I and type II homozygotes, type III homozygotes show increased plasma cystine concentrations after oral cystine load.…”
Section: Introductionmentioning
confidence: 99%
“…highly expressed in renal and intestinal epithelial cells and in brain tissue (Furriols et al, 1993). Initially the Identification of genomic clones.…”
Section: Methodsmentioning
confidence: 99%